PEEL STRENGTH AND ELECTRICAL CONTACT RESISTANCE ANALYSIS OF COPPER TAPE ON CARBON FIBER REINFORCED POLYMER COMPOSITE - Muhammad Zaidan Adhyasa, Rafif
There are several challenges in the ERCM method, one of which is the electrical contact resistance that occurs between the electrode and the composite which will affect the damage detection performance. One of the electrodes used in the ERCM method is a copper tape affixed with adhesion to a Carbon Fiber Reinforced Polymer (CFRP) Composite. Then the strength of the adhesion needs to be measured as well as the change in contact resistance between the CFRP and the copper tape. In this study, the adhesion strength was measured using an experimental method with a 180° peel test following the ISO8510-2:2006 standard and varying the surface roughness of the CFRP by varying the number of sandpaper used, which are #100, #600, and #2000. During peel testing, changes in contact resistance were also measured at certain peel lengths, namely 25mm, 50mm, 75mm, 100mm and 125mm. This experiment aims to see the peel strength of the copper tape and changes in contact resistance and to see the effect of CFRP surface roughness. The experimental results showed that the stripping force of the copper tape on the CFRP fluctuated at each strip length due to the non-uniformity of the surface roughness. The value of the change in contact resistance increases and can be approximated linearly at a strip length of 0-50 mm and exponentially from 50-125 mm. From the analysis, there is an optimum surface roughness for the optimum peel strength and electrical contact resistivity. These results can be used as a reference in ERCM studies with similar electrodes.